Differing Responses to Western Hermeneutics: A Comparative Critical Study of M. Quraish Shihab’s and Muḥammad ‘Imāra’s Thoughts - Sahiron Syamsuddin (Al-Jami'ah Research Centre, 2021)
This article deals with Muslim scholars’ responses to Western hermeneutics and its application to the Qur’an. It focuses on the thoughts of two thinkers, i.e. M. Quraish Shihab from Indonesia and Muḥammad ‘Imāra from Egypt, and discusses them in a comparative critical way. On the basis of the available data, its author comes to the following conclusions. First, the two scholars have different receptions of the Western hermeneutics. While ‘Imāra rejects it totally only because it is rooted in the Western tradition that is different from the Islamic tradition, Shihab accepts it with some considerations on the basis that it can widen horizons of Qur’an interpreters, so that they might understand the Qur’an in a more careful way. Second, ‘Imāra’s arguments for his rejection of it are not strong enough, and even constitute misunderstandings of hermeneutical theories, whereas Shihab’s arguments can be considered more plausible, even though in some cases he does not give enough elaborations. Third, these responses have a certain impact on the dynamics of hermeneutical approaches in Indonesia. [Artikel ini membahas respon ilmuwan muslim mengenai ilmu hermeneutik barat dan penerapannya pada Qur’an. Tulisan ini fokus pada dua pemikir muslim yaitu M. Quraish Shihab dari Indonesia dan Muḥammad ‘Imāra asal Mesir serta mendiskusikannya dalam kerangka perbandingan kritis. Berdasarkan data yang diperoleh menunjukkan bahwa pertama, dua ilmuwan tersebut berbeda dalam penerimaan hermeneutik barat. ‘Imāra menolak sepenuhnya karena berakar pada tradisi barat, sedangkan Shihab menerimanya dengan beberapa pertimbangan selama dapat memperluas cakrawala penafsiran Qur’an dan dapat memahaminya dengan berhati-hati. Kedua, argumen penolakan yang diajukan ‘Imāra tidak cukup kuat dan kadang terdapat kesalahpahaman teoritikal, sedangkan argumen Shihab lebih masuk akal, walaupun dalam beberapa bagian ia tidak memberikan penjelasan lebih lanjut. Ketiga, kedua respon ilmuwan tersebut mempunyai dampak signifikan pada dinamika pendekatan hermeneutik di Indonesia.]